2011
DOI: 10.1080/10810730.2011.551994
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Health Blog Features and Elements by Gender, Occupation, and Perspective

Abstract: This study explores whether there are gender and occupational differences in the health blogosphere and whether there are differences by blogger perspective. Data were derived from content analysis of 951 health blogs identified between June 2007 and May 2008. Results indicate that male, physician bloggers were more likely to have blogs that feature a SiteMeter, sponsorship, and advertising, which also were more prevalent among those blogging from a professional perspective. Women, bloggers in non-health-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Genetics blogs with for-profit affiliations may be viewed as having conflicts of interest related to promoting genetic tools or products with limited or unknown utility. Indeed, conflicts of interest, sponsorship and commercial advertising have been cited as an area of concern for health blogs in general [7]. Anecdotally, we also noted that it was unclear in some cases whether a blog received sponsorship or was otherwise affiliated with an organization or company.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Genetics blogs with for-profit affiliations may be viewed as having conflicts of interest related to promoting genetic tools or products with limited or unknown utility. Indeed, conflicts of interest, sponsorship and commercial advertising have been cited as an area of concern for health blogs in general [7]. Anecdotally, we also noted that it was unclear in some cases whether a blog received sponsorship or was otherwise affiliated with an organization or company.…”
Section: Discussionmentioning
confidence: 96%
“…Google, Yahoo, and Bing) and websites that aggregated science and genetics blogs. Then we used an iterative snowball sampling approach in which additional genetics blogs were identified by following links embedded in already-collected blogs [7]. The process was continued until no more eligible blogs were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on blogs also explores the potential role of blogging in improving health awareness, education, and research (Anonymous, 2009;Boulos, Maramba, & Wheeler, 2006). Some examination of comparatively large samples of health-related blogs has taken place (Clauson, Ekins, & Goncz, 2010;Kovic, Lulic, & Brumni, 2008;Lagu, Kaufman, Asch, & Armstrong, 2008;Miller & Pole, 2009;Miller, Pole, & Bateman, 2011;Wagner, Paquin, & Persky, 2012). By contrast, there has been little systematic research reported on the content and characteristics of mental-health blogs; most of what has been reported consists of small samples focusing on particular mental-health topics and/or populations (Clark & Lang, 2012;Marcus, Westra, Eastwood, & Barnes, 2012;Sundar, Edwards, Hu, & Stavrositu, 2007;Tong, Heinemann-Lafave, Jeon, Kolodziej-Smith, & Warshay, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we examined the content and characteristics of 951 health blogs identified during (Miller & Pole, 2009Miller et al, 2011). Approximately one fifth, or 188 of the 951 blogs analyzed, focused on mental health, including autism spectrum disorder (26.6 percent), bipolar disorder (25.5 percent), eating disorders (22.9 percent), depression (4.8 percent), Down syndrome (4.2 percent), schizophrenia (2.6 percent), and general mental health (13.3 percent).…”
Section: Introductionmentioning
confidence: 99%